The golden standard of the nation: the significance of personifications in the design of national currencies in Eastern Europe - K. I. Shtalenkova (Ukrainian Cultural Studies, 2020)
This article investigates the significance of personifications depicted on national currencies of Eastern Europe in the 19th – 21st cent. Eastern Europe is considered as a region of high research potential due to its status of borderland space with active symbolic struggle on political, socioeconomic and cultural levels. Currency design is an ideological tool that defines collective cultural tradition and historical memory, while national narratives vary in their response to the conditions of their formation. Basing on the visual analysis of money that circulated on the territories of Belarus, Lithuania, Poland, Russia and the Ukraine, the author outlines main categories of human depictions used in the currency design of the states that emerged in the region during the mentioned period. In the 19th cent., most widespread were money of the Russian Empire featuring the emperors and state representation Mother Russia. After the October Revolution in 1917, new states emerged in the region, but no personifications were used in their currency design. Human depictions of that time featured either ordinary people correlating with socialist movements or notable persons denoting political and cultural authenticity of certain state. Another category of human depictions was allegorical feminine figures representing patriarchal values and reproductive resources. Most remarkable examples of this type are Polish coins depicting state representation Polonia (or queen Jadwiga) as well as Polish banknotes with Mother Poland and national heroine Emilia Plater, both issued during the dictatorship of Jósef Piłsudski. Contemporary issues of money use no state representations, preferring instead either notable people, mostly men among them, or introducing other means of cultural representations not related to human depictions. Thus state representations used in the designs of national currencies become less popular in the 21st cent. due to globalisation and de-materialisation of money.